A Study in a Green Supply Chain Management in Mining Industry of Indonesia - Cheisviyanny, Charoline (ExcelingTech, 2020)
Abstract- This research aims to compare Global Reporting Initiative 4 (GRI-G4), and concept of green supply chain management as assessment tools of environmental responsibility. GRI-G4 is a guideline of Sustainability Report preparation which was pioneered by an independent institution in the US. PROPER is an assessment of environmental management issued by The Ministry of Environment of Indonesia. There are five levels in PROPER which are gold, green, blue, red, and black. Green supply chain management is a concept in which a company communicates itself as an environmentally friendly company by taking various actions that contribute positively to the environment and society. The object of this research is a mining company in Indonesia. This company got level ‘gold’ in 2017 and was decreased to level ‘green’ in 2018. The data were documentary data and were analyzed by using content analysis of Sustainability Report 2017 and 2018. The results showed that (1) The assessment of GRI-G4 was in line with PROPER and (2) There were some efforts taken by the company which indicated as implementation of green supply chain management concept in a two-year observation, but it had no impact either on GRI or PROPER assessment. Although this company did not mention itself as a green supply chain management, all of its contributed actions should be rewarded. It suggests considering those efforts in GRI guideline and PROPER assessment.